2016
DOI: 10.1039/c6fd00139d
|View full text |Cite
|
Sign up to set email alerts
|

Towards controlling the dissociation probability by light-induced conical intersections

Abstract: Light-induced conical intersections (LICIs) can be formed both by standing or by running laser waves. The position of a LICI is determined by the laser frequency while the laser intensity controls the strength of the nonadiabatic coupling. Recently, it was shown within the LICI framework that linearly chirped laser pulses have an impact on the dissociation dynamics of the D + 2 molecule (J. Chem. Phys. 143, 014305, (2015); ibid 144, 074309, (2016)). In this work we exploit this finding and perform calculations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 54 publications
(65 reference statements)
1
29
0
Order By: Relevance
“…Numerous theoretical and experimental studies have confirmed that LICIs have noticeable impact on different dynamical properties (like molecular alignment, photodissociation probability, etc...). [14][15][16][17][18][19] Furthermore, a strong effect in the angular distribution of the photofragments has been revealed that serves as a direct signature of the LICI. 18 The first experimental observation of LICIs in diatomic molecules was made by Bucksbaum et al.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous theoretical and experimental studies have confirmed that LICIs have noticeable impact on different dynamical properties (like molecular alignment, photodissociation probability, etc...). [14][15][16][17][18][19] Furthermore, a strong effect in the angular distribution of the photofragments has been revealed that serves as a direct signature of the LICI. 18 The first experimental observation of LICIs in diatomic molecules was made by Bucksbaum et al.…”
Section: Introductionmentioning
confidence: 99%
“…give rise to a variety of unexpected nonadiabatic phenomena in molecules, [30][31][32][33][34] with significant impact on various dynamical [35][36][37][38] and spectroscopic properties. [39][40][41][42] These works were mainly focused on diatomic molecules where the angle between the internuclear axis and the field polarization axis provides the missing degree of freedom for a CI to emerge between two crossing field-dressed PESs.…”
Section: Several Theoretical and Experimental Work Have Demonstratedmentioning
confidence: 99%
“…Thus, it is vital to reveal the characteristic features of these LI-CIs. Previous theoretical studies, employing the classical description of light, investigated the nature of the LICI in diatomic molecules 32,33,[35][36][37][38][39][40] and to what extent the geometric phase of the LICI is similar to the natural CIs for polyatomic molecule in a field free space. 31,[41][42][43] It has been demonstrated that LICI strongly impact the spectroscopic and dynamical properties of molecules, such as the molecular alignment, the photodissociation probability, molecular spectra, and the angular distribution of the dissociation photofragment.…”
Section: Introductionmentioning
confidence: 99%